Antimicrobial and anti-inflammatory activity of Anadenanthera colubrina (Vell.) Brenan (Research, Society and Development, 2020)
The present study aimed to analyze the antimicrobial and anti-inflammatory activity of A. colubrina (Vell.) Brenan extract through a panel of biological activities. The hydroalcoholic extract of A. colubrina was obtained by maceration, which was rotary evaporated and lyophilized. Minimal Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (CFM) tests were performed microdilution against Candida albicans (ATCC 10231 and clinical strain), Candida tropicalis (ATCC 750) and Candida krusei (ATCC 6258). Anti-inflammatory activity was verified by induced paw edema. According to the tests performed, A. colubrina extract showed strong antifungal activity against C. albicans (ATCC 10231) and C. krusei (MIC: 7.81 μg / mL and 31.25 μg / mL, respectively). For the clinical strain of C. albicans and C. tropicalis, antifungal activity was considered weak (MIC: 500 μg / mL and> 2000 μg / mL, respectively). For the CFM tests, the extract showed fungistatic activity on C. albicans strains (ATCC 10231 and clinical strain) and C. tropicalis (CFM:> 1000 μg / mL,> 2000 μg / mL,> 5000 μg / mL, respectively), with fungicidal effect on C. krusei (CFM: 31.25 μg / mL). About the anti-inflammatory activity, among the concentrations of the extract tested, the one administered at the lower dosage presented a greater reduction of the induced paw edema. According to the above, the anti-Candida potential of A. colubrina. It is interesting to carry out studies that can confirm the anti-inflammatory potential of the test plant.